A New Self-Healing Hydrogel Containing hucMSC-Derived Exosomes Promotes Bone Regeneration - Wang, Li; Wang, Jian; Zhou, Xiangbin; Sun, Jie; Zhu, Biao; Duan, Cuimi; Chen, Peng; Guo, Ximin; Zhang, Tong; Guo, Hongyan (Frontiers in Bioengineering and Biotechnology, 2020)
Background Fractures are a medical disease with a high incidence, and about 5–10% of patients need bone transplantation to fill the defect. In this study, we aimed to synthesize a new type of coralline hydroxyapatite (CHA)/silk fibroin (SF)/glycol chitosan (GCS)/difunctionalized polyethylene glycol (DF-PEG) self-healing hydrogel and to evaluate the therapeutic effects of this novel self-healing hydrogel as a human umbilical cord mesenchymal stem cells (hucMSC)-derived exosome carrier on bone defects in SD rat. Methods HucMSCs were isolated from fetal umbilical cord tissue and characterized by surface antigen analysis and pluripotent differentiation in vitro. The cell supernatant after ultracentrifugation was collected to isolate exosomes, which were characterized by transmission electron microscopy and western blot analysis. In vitro cell induction experiments were performed to observe the effects of hucMSC-derived exosomes on the biological behavior of mouse osteoblast progenitor cells (mOPCs) and human umbilical vein endothelial cells (HUVECs). The CHA/SF/GCS/DF-PEG hydrogels were prepared using DF-PEG as the gel factor and then structural and physical properties were characterized. HucMSCs-derived exosomes were added to the hydrogel and their effects were evaluated in SD rats with induced femoral condyle defect. These effects were analyzed by X-ray and micro-CT imaging and H&E, Masson and immunohistochemistry staining. Results HucMSC-derived exosomes can promote osteogenic differentiation of mOPCs and promote the proliferation and migration of HUVECs. The CHA/SF/GCS/DF-PEG hydrogel has a high self-healing capacity, perfect surface morphology and the precipitated CHA crystals have a small size and low crystallinity similar to natural bone minerals. The MTT results showed that the hydrogel was non-toxic and have a good biocompatibility. The in vivo studies have shown that the hydrogel containing exosomes could effectively promote healing of rat bone defect. The histological analysis revealed more new bone tissue and morphogenetic protein 2 (BMP-2) in the hydrogel-exosome group. In addition, the hydrogel-exosome group had the highest microvessel density. Conclusion A self-healing CHA/SF/GCS/DF-PEG hydrogel was successfully prepared. The hydrogel has excellent comprehensive properties and is expected to become a new type of bone graft material. This hydrogel has the effect of promoting bone repair, which is more significant after the addition of hucMSC-derived exosomes.